SMART MULTIPARAMETER INFANT APNOEA MONITOR - Nwaneri, Solomon C.; Ezenwa, Beatrice N.; Osuntoki, Akinniyi A.; Ezeaka, Veronica C.; Gatchell, David W.; Ogunsola, Folasade T. (Asian Journal Of Medical Technology, 2022)
Apnoea is a common disorder in preterm infants who may also suffer from neonatal hypertension. Conventional apnoea monitors used in neonatal intensive care units (NICUs) do not include features for measuring neonatal blood pressure and real-time remote monitoring. Smart devices to monitor this problem in resource-poor environments are expensive and sparsely available. This paper presents the development of a smart multiparameter infant apnoea monitor in a resource-poor setting. The circuit was designed and simulated in Proteus software. The signals were processed using Arduino mega microcontrollers. The microcontroller concurrently communicates apnoea events to the GSM modem and alarm which notify the doctor and caregivers by SMS alert and audible alarm, respectively. Preliminary testing on stable infants at the NICU of Lagos University Teaching Hospital showed promising results. The device can effectively be used to monitor apnoea in infants as well as transmit the results to the doctor in a remote location by SMS. It can also be used to monitor other parameters like oxygen saturation, respiratory rate, heart rate and blood pressure. The documented experiences will provide useful insights for smart infant apnoea monitor development in resource-poor environments.